2012
DOI: 10.1590/s0102-311x2012000900007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and health status self-assessment (SF-36) in the elderly: a population-based study (ISA-Camp 2008)

Abstract: The aim of this study was to determine the association between sleep duration and health status among the elderly. A population-based study was carried out with 1,418 elderly individuals using data from the health survey of Campinas, São Paulo State, Brazil (ISA-Camp 2008

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
1
13
0
12
Order By: Relevance
“…A study conducted with older people, also with data from ISACamp 2008/2009, pointed out a similar result. Lima et al 37 found that women who slept five hours or less per day presented worse mental health, with emotional aspects and vitality harmed in relation to women who slept from seven to eight hours. There are several reports in the literature that the pattern of short sleep is associated with harms to mental health, such as depression, anxiety, mood change, tension, and fatigue 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with older people, also with data from ISACamp 2008/2009, pointed out a similar result. Lima et al 37 found that women who slept five hours or less per day presented worse mental health, with emotional aspects and vitality harmed in relation to women who slept from seven to eight hours. There are several reports in the literature that the pattern of short sleep is associated with harms to mental health, such as depression, anxiety, mood change, tension, and fatigue 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Dünyada yapılan çalışmalarda mutluluğun önemli bir sağlık göstergesi olduğu, sağlık sorunu olmayan yaşlıların daha mutlu olduğu ve mutlu olanların da, daha az sağlık sorunları olduğu bildirilmiştir. 41,42 SONUÇ Bu çalışmada, Kars ve İzmir illeri ASB'lerinden hizmet alan bireylerin polifarmasi oranları arasında anlamlı farklılıklar olduğu görülmüştür. Öğrenim durumu düşük olanlarda polifarmasi oranı oldukça yüksek bulunmuştur.…”
Section: Discussionunclassified
“…For example, large nationally represented studies from Korea (≥ 19 y), 29 Australia (45-74 y) 30 and United States (≥ 18 y) 31 found that both short (≤ 5 h, ≤ 6 h, and ≤ 6 h, respectively) and long (≥ 9 h, ≥ 9 h, and ≥ 8 h, respectively) sleep durations were associated with poor self-reported health status. Conversely, a study conducted among elderly population (> 60 y) in Lima, Peru and a large multi-country study among university students aged 17-30 y found that only short sleep duration (< 6 h and < 7 h, respectively) was associated with poor self-reported health status 32,33 ; whereas Jean-Louis et al found no association between sleep duration and the health-related quality-of-life score in a small sample size (273…”
Section: Introductionmentioning
confidence: 92%